The Importance of Implementing Environment, Social and Government (ESG) and Maqasid Sharia-Based Islamic Finance in Islamic Bank - Agustin, Fitriyana; Muhtadi, Ridan; Sahal, Sakinah (Journal of Islamic Economic Laws, 2023)
Environment, Social & Governance (ESG) is a trending topic worldwide that is gaining a lot of traction because of its focus on social and environmental impact, and its relationship to improving financial performance. Likewise, Islamic Finance, being Shariah-compliant, is also another concept that is growing globally. These two concepts share many common values and similarities as they address challenges of social development. However, there are several obstacles and challenges in terms of integrating ESG in financial institutions, because this is a new concept. Financial institutions implement sharia principles with the aim of achieving Maqasid Sharia (i.e., protecting life, religion, mind, lineage and property). Even in the concept of ESG investment, screening of certain business sectors is required. The aim of this research is to optimize the potential to attract more interest from public companies as ESG and Maqasid Syaria strive to fulfill their social goals without compromising their side business operations. The research method uses a type of Systematic Review with a mixed method of literature search which is carried out both in qualitative and quantitative research. It aims to improve the integrity of research findings from 20 journal articles. This research found that Many Islamic banks have started promoting sustainability through their financing and initiatives many years ago which put them ahead in terms of ESG. There are still many obstacles that need to be overcome to get the best results from the integration of ESG and Islamic Finance as well as offering insights into Islamic finance models such as ESG investment from an Islamic perspective, especially with regard to the concepts of Maqasid Sharia and maslaha mursala, so that ESG and Maqasid Sharia can be applied in all institutions, especially Islamic banking.